2016
DOI: 10.1590/0034-7167.2016690121i
|View full text |Cite
|
Sign up to set email alerts
|

Condições do letramento funcional em saúde de um grupo de idosos diabéticos

Abstract: Objective: to evaluate the conditions of functional health literacy of an elderly diabetics group. Method: cross-sectional and descriptive study, with diabetic's elderly assisted in the SUS (N=114). The social and health conditions were evaluated as well as functional health literacy by S-TOFHLA test (short version); the simple proportions, average, standard deviation and Pearson's Chi-square were described by SPSS software (20.0) with α=5% value. Results: the mean age was 67.4 years, 74.0% of the elderly were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2
30

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 14 publications
3
21
2
30
Order By: Relevance
“…Meta-analysis performed with sixty international studies showed that older age is strongly associated with inadequate HL in studies that assessed comprehension, reasoning and mathematics skills (OR: 4.20; 95%CI) (32) . Older adults are vulnerable regarding HL, especially in relation to cognitive and behavioral skills to manage external resources in such a way that the physical and social well-being is maintained or restored (33)(34) .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis performed with sixty international studies showed that older age is strongly associated with inadequate HL in studies that assessed comprehension, reasoning and mathematics skills (OR: 4.20; 95%CI) (32) . Older adults are vulnerable regarding HL, especially in relation to cognitive and behavioral skills to manage external resources in such a way that the physical and social well-being is maintained or restored (33)(34) .…”
Section: Discussionmentioning
confidence: 99%
“…Testes de rastreamento podem ser utilizados para aferição da literacia em saúde , são necessários para tomadas de decisões (SMITH et al, 2013) e se fazem importantes para mensurar condições específicas de saúde como por exemplo asma, diabetes, hipertensão (BAKER, 2006 (BAKER, 2006;DE OLIVEIRA et al, 2014) DE CASTRO et al, 2014;SOUZA et al, 2014;JUNKES et al, 2015;SANTOS & PORTELLA, 2016;VILELLA et al, 2016a;VILELLA et al, 2016b). Esses instrumentos validados são fundamentais, pois possibilitam a realização de pesquisas com a finalidade de conhecer o nível da literacia em saúde da população brasileira, nas diversas áreas.…”
Section: Resultsunclassified
“…Segundo a Organização Mundial da Saúde (OMS) pode-se definir literacia em saúde como habilidades cognitivas e sociais que determinam a motivação e habilidade dos indivíduos para obter acesso, entender e usar a informação de forma a promover e manter a boa saúde (APOLINARIO et al, 2014). Faz parte dos determinantes sociais da saúde, pois através do desenvolvimento das habilidades necessárias o indivíduo pode otimizar tanto a sua saúde quanto a de seus familiares e da comunidade, sendo um dos caminhos para a promoção da saúde (SANTOS & PORTELLA, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Pesquisadores indianos mostraram maior aderência de mulheres ao AEM com o aumento da escolaridade 32 , o que reforça os achados do estudo aqui apresentado, que encontrou 68,2% de mulheres com hábito de realizar AEM, e 95,7% com ensino fundamental, ou seja, com nove ou mais anos de escolaridade, embora não se tenha observado associação estatística significativa entre as variáveis. O baixo letramento funcional em saúde pode ser condicionante do autocuidado e pode ser influenciado pela baixa escolaridade, pois implica em ter habilidades para compreender e tomar decisões voltadas à autogestão da saúde 33 .…”
Section: Discussionunclassified